Religion–state relations in the perspective of Islamic political theology: Implications for democracy and Indonesian civilization - Bayutama; Amirul Bakhri (PT Perfidia Akademia, 2026)
Studies on religion–state relations in Islamic political theology remain dominated by normative debates, while research connecting theological foundations with their implications for democracy and the development of Indonesian civilization is still limited. This study aims to reconstruct religion–state relations from the perspective of Islamic political theology and examine their implications for democracy and the development of Indonesian civilization. A qualitative approach employing library research was adopted through descriptive-analytical analysis and conceptual synthesis of relevant scholarly literature. The findings demonstrate that Islamic political theology is grounded in tawḥīd, amānah, shūrā, al-'adl, maṣlaḥah, and ukhuwwah, which are reconstructed into a conceptual framework of religion–state relations. These values strengthen accountability, participation, the rule of law, the public interest, and social cohesion within democratic governance. This study contributes by proposing an integrative conceptual model linking Islamic political theology, democracy, and the development of Indonesian civilization. Abstrak Relasi agama dan negara dalam perspektif teologi politik Islam masih didominasi oleh perdebatan normatif, sementara kajian yang menghubungkan landasan teologis dengan implikasinya terhadap demokrasi dan pembangunan peradaban Indonesia masih terbatas. Penelitian ini bertujuan merekonstruksi relasi agama dan negara dalam perspektif teologi politik Islam serta menganalisis implikasinya terhadap demokrasi dan pembangunan peradaban Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research) melalui analisis deskriptif-analitis dan sintesis konseptual terhadap berbagai literatur yang relevan. Hasil penelitian menunjukkan bahwa teologi politik Islam dibangun atas landasan tawḥīd, amānah, shūrā, al-'adl, maṣlaḥah, dan ukhuwwah, yang direkonstruksi menjadi kerangka konseptual relasi agama dan negara. Nilai-nilai tersebut memperkuat akuntabilitas, partisipasi, supremasi hukum, kepentingan publik, dan kohesi sosial dalam demokrasi. Penelitian ini berkontribusi dengan menawarkan model konseptual yang mengintegrasikan teologi politik Islam, demokrasi, dan pembangunan peradaban Indonesia.